2021
DOI: 10.3389/fimmu.2021.763334
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Macrophages in Periodontitis: Characteristics, Function, and Molecular Signaling

Abstract: Periodontitis (PD) is a common chronic infectious disease. The local inflammatory response in the host may cause the destruction of supporting periodontal tissue. Macrophages play a variety of roles in PD, including regulatory and phagocytosis. Moreover, under the induction of different factors, macrophages polarize and form different functional phenotypes. Among them, M1-type macrophages with proinflammatory functions and M2-type macrophages with anti-inflammatory functions are the most representative, and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 189 publications
(241 reference statements)
0
79
0
Order By: Relevance
“…Our previous study has shown that Pg LPS promotes pro-inflammatory cytokine expression, which in turn activates ERK and p38 pathways, thereby promoting macrophage polarization and osteoclast differentiation ( Chang et al, 2021 ). In line with this, pro-inflammatory cytokines such as TNF-α and IL-6 can further accelerate osteoclast maturation ( O'Brien et al, 2016 ; Chang et al, 2021 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 67%
“…Our previous study has shown that Pg LPS promotes pro-inflammatory cytokine expression, which in turn activates ERK and p38 pathways, thereby promoting macrophage polarization and osteoclast differentiation ( Chang et al, 2021 ). In line with this, pro-inflammatory cytokines such as TNF-α and IL-6 can further accelerate osteoclast maturation ( O'Brien et al, 2016 ; Chang et al, 2021 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 67%
“…Macrophages are important parts of the immune system. In periodontitis, macrophages mediate the development and progression of periodontitis through M1 and M2 polarization (97). M1 macrophages produce a series of pro-inflammatory factors including TNF-a and IL-6 to kill bacteria, promote inflammation, and activate osteoclasts that cause absorption of the alveolar ridge.…”
Section: Immune Regulation and Anti-inflammationmentioning
confidence: 99%
“…M1 macrophages produce a series of pro-inflammatory factors including TNF-a and IL-6 to kill bacteria, promote inflammation, and activate osteoclasts that cause absorption of the alveolar ridge. In contrast, M2 macrophages produce anti-inflammatory factors including IL-10 and transforming growth factor (TGF)-b to exert anti-inflammation and angiogenic effects, and activate osteoblasts to restore bone tissue (97)(98)(99). A recent study indicated that PELNs can be absorbed by intestinal macrophages and regulate immune response (86).…”
Section: Immune Regulation and Anti-inflammationmentioning
confidence: 99%
“…P. gingivalis is a putative keystone pathogen with the ability to impair innate immunity and transform a normally symbiotic microbiota into a dysbiotic state in periodontal tissue ( 7 ). Macrophages participate in the initiation of inflammation and are the major immune cells producing pro-inflammatory cytokines and mediating alveolar bone resorption in periodontitis ( 30 ). P. gingivalis induces M1macrophages by downregulating α-KG production ( 19 ), and M1 macrophages were the dominant phenotype for the gingival infiltration in response to P. gingivalis infection ( 31 ).…”
Section: Macrophage Polarization In P Gingivalis -...mentioning
confidence: 99%